Social Defeat Stress Decreases mRNA for Monoamine Oxidase A and Increases 5-HT Turnover in the Brain of Male Nile Tilapia (Oreochromis niloticus) - Higuchi, Yuki; Soga, Tomoko; Parhar, Ishwar S. (Frontiers in Pharmacology, 2019)
Stress induces various neurobiological responses and causes psychiatric disorders, including depression. Monoamine oxidase A (MAO-A) plays an important role in various functions of the brain, such as regulation of mood, anxiety and aggression, and dysregulation of MAO-A is observed in stress-related psychiatric disorders. This study addressed the question whether acute social stress induces changes to transcriptional and/or post-transcriptional regulation of MAO-A expression in the brain. Using male Nile tilapia (Oreochromis niloticus), we investigated whether acute social stress, induced by the presence of a dominant male fish, changes the expression of MAO-A. We measured gene expression of MAO-A by quantitative PCR, enzymatic activity of MAO-A by the luminescent method, and 5-HT and 5-HIAA levels by liquid chromatography–mass spectrometry in the brain of socially stressed and control fish. Socially stressed males showed decreased MAO-A mRNA levels, consistent MAO-A enzymatic activity, increased 5-HT turnover in the brain, and elevated plasma cortisol levels, compared to controls. Our results suggest that acute social stress suppresses the transcription of MAO-A gene, enhances 5-HT metabolism but does not affect the production of MAO-A protein.